تحديات العولمة وتأثيرها على التعليم - عريق, لطيفة; نبار, ربيحة; مقاوسي, كريمة (University of Eloued جامعة الوادي, 2020)
لقد صاحب ظاهرة العولمة تأثير كبير على شتى مناحي الحياة الاقتصادية والسياسية والثقافية، وبذلك فقد اثر النظام العالمي على جل أنظمة المجتمع الواحد، ويوعز تأثر النظام التربوي التعليمي بالعولمة كونه نظام مفتوح يتأثر بأي تغييرات تحدث عبر العالم وهذا التأثير ينعكس بدوره على عناصر النظام التربوي سواء كانت معلم أو تلاميذ أو إدارة، فبما أن العولمة تنشد التطور والرقي الحضاري و المعرفي والمعلوماتي ،فانه كان حري بالمؤسسات التربوية والتعليمية - التي تعاني من ضعف الأداء في إعداد المعلمين وتعليم التلاميذ- أن تتجه إلى تغيير المناهج الدراسية وطرق التدريس وأدوار التلاميذ والمعلمين في العملية التدريسية في الفصل الدراسي، وبغض النظر عن تأثيرات العولمة سلبية كانت أو ايجابية فإن آثارها في الجانب التربوي والتعليمي هي من أخطر سلبيات العولمة التي تؤثر في التعليم بشكل عام وفي المتعلمين بشكل خاص باعتبارهم الغاية المنشودة من التعليم، خاصة وأنه للعولمة آثارها الثقافية والاجتماعية المدمرة التي تهمل الأبعاد الاجتماعية والإنسانية وتزيد التفكك الاجتماعي وتقوم على صياغة ثقافة عالمية مشتركة وتمحو الخصوصية الثقافية للشعوب وصلتها بتراثها وجذور حضارتها وتراثها. Abstract : Globalization has influenced all aspects of economic, political and cultural life. Thus, the global system has affected most of the systems of one society, and instructs the impact of the educational system on globalization as an open system influenced by any changes that occur throughout the world. As globalization seeks to develop and advance civilization, knowledge and information, educational institutions, which suffer from poor performance in teacher preparation and pupils' education, should change their curricula and teaching methods. The roles of students and teachers in the teaching process in the classroom, regardless of the effects of globalization, whether negative or positive, Its effects on the educational and educational side are one of the most serious disadvantages of globalization, which affects education in general and learners in particular as the purpose of education, especially as globalization has devastating cultural and social effects that neglect social and human dimensions and increase social disintegration and is based on the formulation of a common global culture and erase cultural privacy Peoples and their link to their heritage and the roots of their civilization and heritage.
Challenges of globalization and its impact on education
الملتقى الوطني الأول حول المدرسة الجزائرية الإشكالات والتحديات 18- 19 فيفري 2020. جامعة الوادي
Keywords: العولمة، ثقافة العولمة، عولمة الثقافة، العولمة التربوية، تحديات العولمة التربوية; globalization, globalization culture, globalization of culture, educational globalization, challenges of educational globalization.